PERBANDINGAN EFEKTIVITAS DAN BIAYA TERAPI MORFIN MST ORAL DENGAN FENTANIL TRANSDERMAL SEBAGAI TERAPI NYERI KANKER PASIEN RAWAT INAP RUMAH SAKIT KANKER DHARMAIS JAKARTA - , MARLINA INDRIASTUTI; , Dr. Tri Murti Andayani, Sp.FRS., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Cancer pain is a complex problem that may decrease cancer survivorsâ quality of life. A comprehensive cancer pain management is necessary to improve therapy success, including its effectiveness and required costs. This research was aimed at obtaining a description of comparisan of the effectiveness, safety and cost between cancer pain therapy using fentanyl transdermal and sustained release oral morphine at Dharmais Cancer Hospital (RSKD) The research belongs to descriptive research using retrospective data collection obtained from data investigation to patientsâ medical record and cost of medical use data. The subjects of the research were solid cancer inpatients who met the inclusion criteria at RSKD from January until December 2011. Effectiveness data were obtained from the measurement of pain scale using Visual Analogue Scale (VAS) recorded in medical record. The effectiveness data were analyzed based on the percentage of the research subjects who achieved mild scale within less than 7 days (therapy target). Therapy cost included therapy group cost, adjuvant therapy cost and adverse event cost. Mann Whitney test was conducted to identify the comparison of the average of pain therapy cost, which achieved therapy target. The effectiveness of fentanyl transdermal was higher (45.24%) than that of sustained release oral morphine (31.58%). The precentage of the occurence of constipation and nausea/vomiting on fentanyl transdermal was 26.19% dan 7.12% and on sustained release oral morphine was 47.38% dan 7. 89%. The total cost of the average of fentanyl transdermal and sustained release oral morphine until achieving the therapy target were Rp 449,544.11Â± Rp 433,371.00 and Rp365,403.17Â± Rp 267,452.00 (p=0.465).